Description Of The Dynamics Of Morphological Changes In The Liver And Small Intestine Of Laboratory Animals Under Acute Irradiation - Sultonova L.D. (Genius Publishing Group, 2022)
Acute irradiation-depends on the frequency and duration of ionizing radiation, develops to a different extent depending on the radiation sensitivity of the organs. In acute irradiation, the most sensitive organs are members of the immune system (thymus, bone marrow, spleen, lymph nodes), mucous membranes of the gastrointestinal tract, exoskeletal and endocrine glands (pituitary, thyroid gland, adrenal gland), sex glands (ovaries, testes, prostate gland). Members with low sensitivity to radiation include the heart, kidneys, liver, head and back muscles, bone tissue, joints [2]. In the process of irradiation, the biological tissue membrane is in a state of destabilization: an increase in membrane permeability leads to increased activity of freely located proteins in the cytoplasm due to the abundant penetration of fluid into the cell and various micro - and Macroelements, includingsiysium ions, damage to intracellular structures of lysosomal enzymes, and the development of hydropic dystrophy in the epithelium of Exactly as a result of venous fullness in the liver tissue, hypoxia of hepatocytes leads to the development of large, medium and small drop fatty dystrophy [5].
Keywords: Liver; organs; penetration; enzymes